Access to clean energy in Africa revisited: The roles of women empowerment, corruption control, FDI and sectoral growth. - Kwame Adjei-Mantey; Paul Adjei Kwakwa; Eleazer Ankrah (PLoS ONE)
One of the key contributors to climate change is energy consumption, with the type of energy used having implications on the natural environment and health of users. To promote environmental sustainability and sustainable development, Sustainable Development Goal (SDG) 7 aims to achieve accessibility, and affordability of clean and modern forms of energy for all. This study aims to investigate the effects of women empowerment, corruption control, foreign direct investment, and sectoral growth on access to clean energy in Africa, as well as the effects of the interrelatedness of these factors on clean energy access. Using data on 32 countries in Africa from 2002 to 2021 and rigorous econometric techniques, the study finds that women empowerment and corruption control significantly increase access to clean energy in Africa while sectoral analyses show varying effects of growth in the different sectors on clean energy accessibility. Furthermore, it is found that corruption control is not able to reverse situations of adverse effects of some variables on access to clean energy in some cases, likely due to the low levels of corruption control in Africa. The results suggest that African countries could enhance access to clean energy for its citizens and harness the full potential of clean energy, to promote sustainable development and improve the lives of their population, by empowering women, fighting corruption, and cultivating balanced economic growth.